Religious Distance in Croatia - Marinović-Jerolimov, Dinka (Array, 2001)
The paper presents the results from the research "Religious changes and values in Croatian society" conducted in the Zagreb region (1999) on religious distance between Catholics, Muslims, Jews, Orthodox, Baptists, Adventists, Evangelicals, Mormons, Jehovah's Witnesses and Hare Krishnas. Religious distance was measured through acceptance or rejection of marriage, friendship, neighbourhood, working and living in the same state with the members of listed groups. The analysis shows: the acceptance of marriage only to Catholics; the rejection of marriage to members of all other groups; the smallest distance to Catholics; the biggest distance to Hare Krishna members; bigger religious distance among religious respondents, regular religious practicants, less educated, farmers, workers, and small towns inhabitants. Dominant Catholic identity helps us to understand different levels of religious distance.